Woloch, Muller V. Oregon - A Brief History With Documents - Cole, Jeffery (Teaching History: A Journal of Methods, 2001)
Nancy Woloch’s Muller v. Oregon is another gem in the Bedford Series in History and Culture. Like its sister volumes, Woloch’s work is well crafted for effective classroom use. Her focus is the important 1908 Supreme Court case involving protective labor laws brought by the owner of an Oregon laundry.